2012
DOI: 10.2139/ssrn.2115537
|View full text |Cite
|
Sign up to set email alerts
|

Did Capital Requirements and Fair Value Accounting Spark Fire Sales in Distressed Mortgage-Backed Securities?

Abstract: and NBER. We thank seminar participants at Brigham Young University for helpful comments. The analysis and conclusions contained in this paper are those of the authors and do not necessarily reflect the views of the Board of Governors of the Federal Reserve System, its members, its staff, or the National Bureau of Economic Research. NBER working papers are circulated for discussion and comment purposes. They have not been peerreviewed or been subject to the review by the NBER Board of Directors that accompanie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 34 publications
3
30
0
Order By: Relevance
“…The fact that life insurers (under HCA) rather than P&C (facing MTM for speculative-grade bonds) exhibit larger realized, as well as unrealized, losses is inconsistent with the notion that systemic risk is always amplified by the fire-sale feedback problem associated with MTM. To be clear, P&C insurers do sell downgraded securities (see Ellul et al (2012) and Merrill et al (2012)), but this evidence suggests that, on average, the implications for realized losses were actually relatively less pronounced for P&C firms than for life firms.…”
Section: Evolution Of Rbc Ratios Before and During The Crisismentioning
confidence: 99%
See 1 more Smart Citation
“…The fact that life insurers (under HCA) rather than P&C (facing MTM for speculative-grade bonds) exhibit larger realized, as well as unrealized, losses is inconsistent with the notion that systemic risk is always amplified by the fire-sale feedback problem associated with MTM. To be clear, P&C insurers do sell downgraded securities (see Ellul et al (2012) and Merrill et al (2012)), but this evidence suggests that, on average, the implications for realized losses were actually relatively less pronounced for P&C firms than for life firms.…”
Section: Evolution Of Rbc Ratios Before and During The Crisismentioning
confidence: 99%
“…Indeed, when an institution's RBC ratio falls below certain thresholds, it is put on a regulatory watch and immediate action must be taken. It is important to note that both types of accounting rules, MTM and HCA, have important effects on the calculation of the RBC ratio (see Ellul et al (2012) and Merrill et al (2012)) because they may directly or indirectly impact both the numerator (equity capital) and the denominator (required capital) of this-ratio. The accounting rules governing the recognition of portfolio assets (or book values) have clear implications for equity capital.…”
mentioning
confidence: 99%
“…Our work is also related to the literature on financial and regulatory frictions on the supply side of insurance markets. In particular, some recent papers show that capital regulation and accounting rules, when they interact with financial frictions, affect investment behavior on the asset side of the balance sheet (Merrill, Nadauld, Stulz, and Sherlund (2012), Becker and Opp (2013), Becker and Ivashina (2015), Ellul, Jotikasthira, Lundblad, and Wang (2015)). Our work complements this literature by showing that a set of capital regulation and accounting rules on the liability side has a profound impact on reinsurance activity and pricing behavior in the retail market (Koijen and Yogo (2015)).…”
Section: Introductionmentioning
confidence: 99%
“…In parallel, other studies have shown that securitised and structured finance products, such as Collateralised Debt Obligations (CDOs) and subprime Residential Mortgage Backed Securities (RMBS), were responsible for the intensification and severity of the recent crisis. 4 As downgrades of these structured securities spiked in 2007 their prices plunged, while the buy side almost disappeared (for losses on RMBS, see, Merrill et al, 2012). The RMBS market has been shown to be the origin of contagion during the crisis and so represented a source of considerable risk for banks relating to increasing risk aversion and market illiquidity (Fender and Scheicher, 2009;Longstaff, 2010).…”
Section: Introductionmentioning
confidence: 99%